A Study On Art And Architecture Of Megalithic Culture With Special Reference To Andhra Pradesh (Journal of Namibian Studies : History Politics Culture, 2022)
The Megalithic culture, recognized for its monumental stone constructions, represents a significant phase in human architectural and artistic evolution. This study delves into the art and architecture of the Megalithic period with a focused examination of Andhra Pradesh. By analyzing archaeological findings, structural designs, and artistic motifs prevalent in this region, the research aims to elucidate the cultural, social, and technological aspects that influenced Megalithic constructions. The study incorporates data from various excavation sites, comparative analysis with other regions, and reviews existing scholarly work to provide a comprehensive understanding of the subject. The findings highlight the distinctive features of Andhra Pradesh’s Megalithic architecture and its contribution to the broader Indian Megalithic tradition.